2021
DOI: 10.1007/s00338-021-02090-1
|View full text |Cite
|
Sign up to set email alerts
|

Neighboring colonies influence uptake of thermotolerant endosymbionts in threatened Caribbean coral recruits

Abstract: Intervention strategies to enhance coral resilience include manipulating the association between corals and their algal endosymbionts. While hosting thermotolerant Durusdinium trenchii can increase bleaching thresholds in adults, its effects remain largely unknown during the early life stages of Caribbean corals.Here, we tested if Orbicella faveolata recruits could establish symbiosis with D. trenchii supplied by nearby "donor" colonies and examined the resulting ecological trade-offs to evaluate early Symbiod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 86 publications
1
14
0
Order By: Relevance
“…These results suggest the complex role of larval aggregation in shaping post-settlement performance of corals in response to ocean warming and acidification, and provide direct evidence for the benefits and tradeoff associated with coral chimerism in determining the recruitment success under future climate change. Uptake of algal symbionts and symbiosis establishment are of paramount importance to the early success and resilience of broadcast spawning corals (Suzuki et al, 2013;Yuyama and Higuchi, 2014;Hazraty-Kari et al, 2022), while this process is particularly susceptible to the ongoing ocean warming (Abrego et al, 2012;Yuyama et al, 2016;Yorifuji et al, 2017;Sun et al, 2020;Jiang et al, 2021;Williamson et al, 2021). Consistent with these aforementioned studies, our results also showed detrimental effects of heat stress on symbiont infection process, with symbiont infection rates being reduced by 50% at 30.5°C.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results suggest the complex role of larval aggregation in shaping post-settlement performance of corals in response to ocean warming and acidification, and provide direct evidence for the benefits and tradeoff associated with coral chimerism in determining the recruitment success under future climate change. Uptake of algal symbionts and symbiosis establishment are of paramount importance to the early success and resilience of broadcast spawning corals (Suzuki et al, 2013;Yuyama and Higuchi, 2014;Hazraty-Kari et al, 2022), while this process is particularly susceptible to the ongoing ocean warming (Abrego et al, 2012;Yuyama et al, 2016;Yorifuji et al, 2017;Sun et al, 2020;Jiang et al, 2021;Williamson et al, 2021). Consistent with these aforementioned studies, our results also showed detrimental effects of heat stress on symbiont infection process, with symbiont infection rates being reduced by 50% at 30.5°C.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with these aforementioned studies, our results also showed detrimental effects of heat stress on symbiont infection process, with symbiont infection rates being reduced by 50% at 30.5°C. It is important to note that the experimental inoculation method used here may differ from what would happen on natural reefs with a high diversity of free-living Symbiodiniaceae, and this could greatly influence the symbiont selection and acquisition in early stages of corals (Williamson et al, 2021;Matsuda et al, 2022). Furthermore, we found a significant interaction between increased temperature and pCO 2 on algal uptake.…”
Section: Discussionmentioning
confidence: 80%
“…If a specific taxon (i.e. Breviolum ) is implicated in SCTLD infection, managers may choose to provide recruits with sources of alternative taxa during initial symbiosis establishment (Williamson et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…After settlement, recruits were provisioned with Symbiodiniaceae. Fragments of Orbicella faveolata hosting Durusdinium trenchii were placed in aquaria with D. labyrinthiformis recruits to serve as symbiont sources (Williamson et al, 2021). The C. natans recruits were inoculated with approximately one million cells per liter of cultured Breviolum and D. trenchii twice per week, until all recruits were visibly infected (approximately three weeks).…”
Section: Methodsmentioning
confidence: 99%
“…Stress memory in corals was first discovered in eastfacing surfaces of small massive corals that bleached during a summer heatwave whereas west-facing surfaces receiving higher light dosesdid not [50]. Whilst some studies have since demonstrated that moderate thermal [51][52][53] and acidification [54] stress can also enhance tolerance to subsequent thermal stress, others have shown pre-conditioning is not a guarantee to boosting stress tolerance [55]. On balance, given the potential for enhancing stress tolerance through careful environmental exposure, preconditioning seems useful for reef restoration during the larval and early recruit rearing phase of sexually produced coral stock, but also for asexual adult propagation by carefully choosing the location of in situ nurseries (Propagation and planting).…”
Section: Manipulations Targeted At the Coral Hostmentioning
confidence: 99%